Penokohan dalam Twelve Years A Slave: Pesan Solidaritas Melawan Perbudakan - Hutapea, Rizky Utami (UI Scholars Hub, 2015)
Prejudice and discrimination at the time of slavery is one of the significant factors that constructs racism against African-Americans until today. This journal will discuss about prejudice and discrimination at the time of slavery which is reflected in the characterizations of the black characters and the white characters in Twelve Years A Slave. The analysis method of this juronal is by colaborating close reading with prejudice theory of Pettigrew (1982) and Healey (1998). The characterizations that are shown in the slave narrative Twelve Years A Slave are very diverse and do not stereotyping the characterizations based on the color of their skin. Solomon as the author and narrator criticizes slavery in not racist way. He tends to criticize the system of slavery without blaming the white race. The diversity of characterizations reflected a message of solidarity to fight against slavery.